Hydroxyurea-induced foot ulcer in a case of essential thrombocythaemia. - Tsuchiya S; Ichioka S; Sekiya N (Journal of Wound Care, 2010)
Objective: To illustrate the association between hydroxyurea and the development of ulcers. Method: A case study is presented, in which histological changes, mean corpuscular volume (MCV) and transcutaneous oxygen tension (TcPO2) were all measured and analysed, both during hydroxyurea treatment and following it's discontinuation. Results: Two months following the cessation of hydroxyurea therapy, the patient's ulcer had healed completely. Biopsy specimens taken before and after its discontinuation showed a considerable improvement in vascularity, with a capillary density 6.28 times higher after discontinuation of the drug. TcPO2 was just 8mmHg at the first measurement, and this increased to 65mmHg at the second. Conclusion: These findings suggest deficient neovascularisation and circulation during hydroxyurea treatment. Changes in MCV also appeared to have an effect on the progress of wound healing, which supports the hypothesis that macroerythrocytosis may be involved in the development of these rare ulcers, via impairment of the microcirculatory rheology. Conflict of interest: None.